2019
DOI: 10.1002/brb3.1233
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of neurocognitive profiles in a community cohort living in marginal housing

Abstract: Objective We investigated white matter differences associated with distinct neurocognitive profiles derived from a large cohort of marginally housed persons with comorbid physical and mental illnesses. Our prior work identified three profile cluster groups: a high functioning group (Cluster 1), a low functioning group with relative strength in decision‐making (Cluster 3), and an intermediary group with a relative decision‐making weakness (Cluster 2). This study extends previous findings of cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Total scores range from 12 (very fluent in English) to 60 (not at all fluent in English), and those with a score of 24 (much fluent in English) or lower were included in analyses. These details of the cognitive assessment protocol have been previously published [6,8,9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total scores range from 12 (very fluent in English) to 60 (not at all fluent in English), and those with a score of 24 (much fluent in English) or lower were included in analyses. These details of the cognitive assessment protocol have been previously published [6,8,9].…”
Section: Methodsmentioning
confidence: 99%
“…Common co-occurring illnesses include psychosis, polysubstance use, HIV infection, and traumatic brain injury [24], which may reflect a set of genetic, environmental, and developmental vulnerabilities that predispose individuals to significant cognitive dysfunction. Previous studies in marginalized populations have shown substantial cognitive heterogeneity and impairment across domains [57] and this was linked with regional alterations in cortical thickness and gyrification [8], and to variation in white matter microstructure [9]. However, due to the scope of illness burden among marginalized persons, there are likely to be more widespread alterations to structural brain integrity, which warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%